2008
DOI: 10.1111/j.1600-0420.2007.00994.x
|View full text |Cite
|
Sign up to set email alerts
|

The comparative study of two recently developed A‐scan devices: determination of central corneal thickness, anterior chamber depth and axial length

Abstract: . Purpose:  The clinical use and comparison of two recently developed A‐scan ultrasound devices. Methods:  The same investigator determined central corneal thickness (CCT), anterior chamber depth (ACD) and axial length (AL) with an OcuScan RxP (Alcon, Forth Worth, Texas, USA) and an AL‐2000 (Tomey, Erlangen, Germany) ultrasound device in 80 eyes of 40 patients. The mean patient age was 63.72 years [standard deviation (SD) 18.92]. The patients did not suffer from any systemic or eye disease affecting the anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…The ultrasound pachimetry measurements GHD, growth hormone deficiency; SD, standard deviation. obtained in our study's control group correlate well with those described previously (Sohajda et al 2008).…”
Section: Discussionsupporting
confidence: 91%
“…The ultrasound pachimetry measurements GHD, growth hormone deficiency; SD, standard deviation. obtained in our study's control group correlate well with those described previously (Sohajda et al 2008).…”
Section: Discussionsupporting
confidence: 91%
“…However, the 20 consecutive measurements were conducted by a single experienced observer using the same device under the same physical conditions and no difference was detected between the baseline and 3-month measurements obtained in the control group, which indicates a good reproducibility. Moreover, Sohajda et al (2008) found a positive significant correlation between measurements obtained with different A-scan instruments.…”
Section: Discussionmentioning
confidence: 76%
“…This device is reliable in clinical use and we also applied this system for A-scan biometry. 28 Biometry was performed at the end of the measurements to avoid its probable influence on the other imaging modalities due to corneal flattening after applanation with the ultrasound probe. The mechanism of this device and its measurement method has been discussed in other studies.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of this device and its measurement method has been discussed in other studies. 28 Before performing A-scan ultrasonography, in order to anesthetize the cornea, one drop of tetracaine 0.5% (Anestocaine; Sina Darou, Iran) was instilled in each eye. Since there was no study to assess the repeatability of ultrasound biometry in the KCN eyes, the measurements were repeated three times (10 results for each measurement) per eye and the mean value of the measurements was recorded.…”
Section: Methodsmentioning
confidence: 99%